(untitled) (Research, Society and Development, 2022)
In the socio-environmental focus, this article complies with the guidelines of the Correios Progress Communication Report (COP), which sought to analyze the management of tires in its own fleet or at the service of ECT in Bahia, considering the environmental and social responsibilities assumed in the Report. 2014-2015 “Correios Progress Communication” and the “Correios 2020” Strategic Plan. Based on the adopted processes, parameters were established that allow the perception of impacts in the continuous search for feasibility and minimization of liabilities, from sensitization of process executors to the economy of services and products, reverse logistics of solid waste (disposal); technological routes (reuse, recycling); current legislation; selective collection and sustainable consumption). An exploratory, descriptive research was carried out, adopting the case study strategy, systematizing observations, official public data and information obtained through semi-structured interviews, with aspects related to tire disposal logistics being explained. Weaknesses were observed in the post-use tire disposal chain at ECT/SE/BA, in disagreement with the COP, PGRS and Strategic Plan "Correios 2020", incurring the generation of environmental liabilities and consequently socioeconomic losses, compromising the vision established in “Being a World Class Company” and having Sustainability (Social/Environmental/Economic) one of its strategic values.